2022
DOI: 10.1590/1413-81232022276.15062021
|View full text |Cite
|
Sign up to set email alerts
|

Financiamento da saúde e dependência fiscal dos municípios brasileiros entre 2004 e 2019

Abstract: Resumo Este artigo descreve a evolução do financiamento municipal do Sistema Único de Saúde, de 2004 a 2019, considerando receitas e despesas de fontes próprias e não-próprias, analisa a redistribuição fiscal, de acordo com o porte populacional e a renda média domiciliar, e compara essa evolução em dois períodos, caracterizados como de crescimento econômico (2004-2014) e de recessão (2015-2019). O estudo se baseou em dados do Sistema de Informações sobre Orçamentos Públicos em Saúde. Constatou-se crescimento r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
9

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 12 publications
1
7
0
9
Order By: Relevance
“…Still about how intergovernmental transfers and municipal resources differ in terms of the response to economic fluctuation, the findings of Cruz, Barros and Souza (2022) somehow complement the evidence provided here. The authors found that the fiscal dependence of Brazilian municipalities regarding the financing of public health services, given by the increase in intergovernmental transfers, increased after the economic recession.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Still about how intergovernmental transfers and municipal resources differ in terms of the response to economic fluctuation, the findings of Cruz, Barros and Souza (2022) somehow complement the evidence provided here. The authors found that the fiscal dependence of Brazilian municipalities regarding the financing of public health services, given by the increase in intergovernmental transfers, increased after the economic recession.…”
Section: Discussionsupporting
confidence: 76%
“…The results indicate that the most populous municipalities show a more pro-cyclical behavior than the smallest municipalities. This difference is more pronounced for municipal health resources than for intergovernmental health transfers, which may be related to the fact that smaller municipalities are in a process of increasing both fiscal and health financing dependence on intergovernmental transfers (Cruz, Barros and Souza, 2022).…”
Section: Discussionmentioning
confidence: 97%
“…Esse fato foi observado nos últimos anos (2018 e 2019), no qual a participação percentual da receita de impostos próprios no município de Vitória sofreu decréscimo, passando de 54% em 2017 para 52,38% em 2018 e 49,34% em 2019, reduzindo o montante de recursos próprios municipais para execução da política de saúde. Esse movimento pode estar articulado à baixa arrecadação de impostos por parte do município e às oscilações na economia nacional (Cruz;Barros;Souza, 2022).…”
Section: Receita Da Saúde No Município De Vitóriaunclassified
“…Esse resultado pode apontar o aumento da dependência fiscal do município em relação à União. De acordo com Cruz, Barros e Souza (2022), esse panorama de dependência das transferências federais foi "[...] agravado com a aprovação de emendas constitucionais que limitaram a autonomia municipal no desenvolvimento de mecanismos locais de tributação" (Cruz;Barros;Souza, 2022, p. 2.465).…”
Section: Receita Da Saúde No Município De Vitóriaunclassified
“…In Brazil, a context of fiscal austerity, in place since implementation of the national health service (SUS) began, strains federative relations and impacts health management in municipalities of all sizes. Funding is recognised to be one of the factors that directly influence the decisions of local SUS managers, due to the availability of both local funds and those transferred by the federal government [1][2][3] . The fiscal regime 4 introduced by Constitutional Amendment No.…”
Section: Introductionmentioning
confidence: 99%